2007
DOI: 10.1002/ldr.797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wildfire, salvage logging and slash treatments on soil degradation

Abstract: The effect of wildfire and the subsequent harvesting on soil degradation was evaluated in a burned Pinus pinaster stand in Galicia (NW Spain). During the first year following a fire of moderate intensity, burned trees were not harvested and soil erosion losses, measured by sediment collection at the bottom of bordered plots, were very low. An apparently limited impact of fire on soil and reduced rainfall erosivity for this period could be responsible for that result.Salvage logging took place 13 months after f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 52 publications
5
47
0
2
Order By: Relevance
“…The effectiveness of a Pine needle "carpet" to reduce post-fire erosion was suggested by Shakesby et al (1993), and was later confirmed by Pannkuk and Robichaud (2003), Cerdà and Doerr (2008) and Neris et al, (2013) through laboratory and field rainfall simulation experiments. Besides fire severity, also postfire logging (Fernández et al, 2007;Malvar et al, 2013) could contribute to the comparatively high specific sediment losses in Prats (2013a).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of a Pine needle "carpet" to reduce post-fire erosion was suggested by Shakesby et al (1993), and was later confirmed by Pannkuk and Robichaud (2003), Cerdà and Doerr (2008) and Neris et al, (2013) through laboratory and field rainfall simulation experiments. Besides fire severity, also postfire logging (Fernández et al, 2007;Malvar et al, 2013) could contribute to the comparatively high specific sediment losses in Prats (2013a).…”
Section: Figmentioning
confidence: 99%
“…This includes certain tree-logging practices (Fernández et al, 2004(Fernández et al, , 2007Malvar et al, 2013) as well as rip-ploughing in downslope direction (Shakesby et al, 2002;Terry, 1996). The sediment losses following terracing observed in this study were clearly less than the 37 Mg ha -1 y -1 following downslope rip-ploughing reported by Shakesby et al (2002) but they did amount to 24 Mg ha -1 y -1 in the case of the Eucalypt site.…”
Section: Overall Erosion Assessmentmentioning
confidence: 99%
“…In modern forestry, wildfires are considered undesirable, because fire destroys vegetation cover and reduces soil fertility due to erosion and nutrient losses (Fernández et al 2007). Fires affect physical, chemical and biochemical soil properties, primarily by transferring heat into soil.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, they can become a significant cause of land degradation (Maselli et al, 2000;Alloza et al, 2006;Fernandez et al, 2007). As a response to this concern, numerous studies have analyzed aspects related to fire behaviour, its suppression and effects (Barrett, 1988;Fryer and Johnson, 1988).…”
Section: Introductionmentioning
confidence: 99%